2018
DOI: 10.1155/2018/4718045
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Drug Release Study of Novel Nanopharmaceuticals with Polysorbate 80 Surface Adsorption

Abstract: Most free drugs that cross the blood-brain barrier are characterized by high liposolubility, but they often have limited clinical applications because of poor dissolution and poor bioavailability. In this study, we prepared donepezil drug-loaded nanoparticles (DZP) with cholesterol-modified pullulan (CHP) as the nanocarrier (DZP-CHP) and surface modified the drugloaded nanoparticles to improve the water solubility of donepezil while enhancing its targeting and sustained release. We determined the drug loading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…Most drugs for AD treatment, including DPZ, are designed to be highly hydrophobic because the target region of these drugs is usually inside the brain; therefore, these drugs are designed to pass through the blood-brain barrier (BBB). Only hydrophobic and small molecule drugs can go through the BBB by blood circulation system [37,38]. DPZ is the leading compound for the treatment of AD in more than 50 countries.…”
Section: Discussionmentioning
confidence: 99%
“…Most drugs for AD treatment, including DPZ, are designed to be highly hydrophobic because the target region of these drugs is usually inside the brain; therefore, these drugs are designed to pass through the blood-brain barrier (BBB). Only hydrophobic and small molecule drugs can go through the BBB by blood circulation system [37,38]. DPZ is the leading compound for the treatment of AD in more than 50 countries.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of the grafted P123 or a high content of P123 in the CP copolymer contributed to enlarging the CMC value. Many previous studies have also shown that conjugation with polysaccharides leads to a reduction of the CMC value of pluronics [6,32]. Chitosan attacks pluronic chains and shields the hydrophobic blocks from interaction with water reducing the interfacial free energy of the polymer-water system.…”
Section: Characterization Of Micelle and Nanogel Formationmentioning
confidence: 95%
“…), fluorescent probes (pyrazole, etc. ), or genes/proteins can be protected by the hydrophilic segments organizing into the shell, whereas the pharmacokinetics of this compound become more significant [3][4][5][6][7]. Along with the advantage of a core-shell nanostructure, the introduction of natural polymers such as chitosan, heparin, or hyaluronic acid also helps to protect nanoparticles from opsonization due to the imparting of a stealth effect on the shell [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The higher particle size of the alginate NPs negatively affects the rate of release of P and K; because with high particle size, the specific surface area of the NPs is reduced, and, therefore, the solubility and dissolution rate can be decreased [33]. a Data correspond to the carbonisation of alginate.…”
Section: Release Of P and K With The Addition Of Enzymesmentioning
confidence: 99%